2021
DOI: 10.22373/ej.v9i1.9127
|View full text |Cite
|
Sign up to set email alerts
|

EFL teachers’ online teacher professional development experiences amidst the COVID-19 pandemic: Practices and perceptions

Abstract: This research investigates the EFL teachers’ practices and perceptions of online teacher professional development (OTPD) experiences to improve their competencies for teaching online language learning amidst the COVID-19 pandemic. 42 EFL teachers voluntarily became the participants through invitation. All participants were requested to give responses on a questionnaire. Eight participants were then invited for an individual semi-structured interview. Descriptive statistics were employed to analyze the question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…Even though emergency remote teaching completely different from traditional or offline learning and may occurred several problems as mentioned by Khlaif et al(2021) in his research findings that most of EFL students" engagement during covid-19 in Palestine reported that online learning has broaden digital inequality and threaten their digital privacy which negatively influence their engagement Almost the same problems also occurred in the study from Atmojo (2021) who analyzed EFL teachers" online professional development experiences amidst the COVID-19 pandemic that the finding stated that the problems mentioned such as (1) instability internet connection; (2) time limited; (3) shortage of internet quota; (4) lack of interaction; (5) and limited facilities and infrastructure.…”
Section: Behavioral Engagementmentioning
confidence: 69%
“…Even though emergency remote teaching completely different from traditional or offline learning and may occurred several problems as mentioned by Khlaif et al(2021) in his research findings that most of EFL students" engagement during covid-19 in Palestine reported that online learning has broaden digital inequality and threaten their digital privacy which negatively influence their engagement Almost the same problems also occurred in the study from Atmojo (2021) who analyzed EFL teachers" online professional development experiences amidst the COVID-19 pandemic that the finding stated that the problems mentioned such as (1) instability internet connection; (2) time limited; (3) shortage of internet quota; (4) lack of interaction; (5) and limited facilities and infrastructure.…”
Section: Behavioral Engagementmentioning
confidence: 69%
“…It is is self-initiated and may use informal channels such as social media and other networks to collaborate and share. As other researchers have suggested, for example (Atmojo, 2021;Nugroho & Haghegh, 2021), joining professional development programs was instrumental in helping teachers to cope with the unprecedented requirement of teaching in the global pandemic context.…”
Section: Teachers' Expectations Of Professional Development Programmentioning
confidence: 99%
“…And for the last is, all of the participant is have a willingness to continue to develop professionally. (Evişen, 2021) The next journal was entitled EFL teachers' online teacher professional development experiences amidst the COVID-19 pandemic: Practices and perceptions by Arief Eko Priyo Atmojo (2021). The article aimed at investigating the EFL teachers' practices and perceptions of online teacher professional development (OTPD) experiences to improve their competencies for teaching online language learning amidst the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It because, some of EFL teachers still lack competence in teaching online language learning. (Atmojo, 2021) The last journal entitled PRIMARY ENGLISH TEACHERS PROFESSIONAL DEVELOPMENT DURING COVID19 PANDEMIC: A PRELIMINARY RESEARCH and it's conducted by Wiputra Cendana and Yonathan Winardi. This study was aimed to investigating professional development (PD) for language teachers during pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%